PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN MEDIA WORD WALL UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI PANCASILA DALAM KEHIDUPANKU KELAS V SD NEGERI JONO - Ulnatifah, Rahma; Anjarini, Titi; Khaq, Muflikhul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the application of the make a match learning model assisted by word wall media in pancasila education subjects to increase the activeness and learning outcomes of grade V students of SD Negeri Jono, describe the increase in activeness and learning outcomes of students through the make match learning model in class V pancasila education learning at SD Negeri Jono. This research jnis is Classroom Action Research. The subjects of this study were grade V students of SD Negeri Jono. Data analysis techniques use qualitative and quantitative analysis. The results of this study showed that the acquisition of data on the implementation of cycle I learning obtained 73.9%, cycle II increased by 80% with the achievement of 80% success indicators. The make a match learning model has an effect on increasing student activeness in the pre-cycle stage obtaining 44%, cycle I 50.5%, cycle II increasing 79.5%. Pre-cycle learning outcomes obtained 23.5%, cycle I 35.2%, cycle II rose 88.2%. Based on these results. So word media is proven to be able to improve student learning outcomes.